Prolotherapy for early osteoarthritis knee - Jain, Sarvesh; Jain, Rajesh; Arora, KK (International Journal of Medical Research and Review, 2014)
Introduction: Osteoarthritis is most prevalent arthritis in older patients. Present study is to evaluate efficacy of dextrose prolotherapy for treatment of early knee osteoarthritis. Material & Method: This study was done at Bundelkhand Medical College, Sagar. In our study we studied 38 patients of more than 55 years of age. For treatment of Knee OA, 3 sitting of prolotherapy were given one month apart and patient followed up for 1 year. Results: 76% patients showed improvement on second follow-up. On third follow up 89% showed improvement. On further follow up at 6 months 81% of patients were symptomatically improved. These patients remained symptomatically better even at the conclusion of study. Discussion: Definitive mechanism of action of prolotherapy is unknown but probable mechanism is, hypertonic dextrose induced growth factor release and connective tissue healing thereafter. Conclusion: Dextrose prolotherapy injection is safe, reliable and long lasting treatment modality for early osteoarthritis